New multiplex PCR methods for rapid screening of genetically modified organisms in foods - Datukishvili, Nelly; Kutateladze, Tamara; Gabriadze, Inga; Bitskinashvili, Kakha; Vishnepolsky, Boris (Frontiers in Microbiology, 2015)
We present novel multiplex PCR methods for rapid and reliable screening of genetically modified organisms (GMOs). New designed PCR primers targeting four frequently used GMO specific sequences permitted identification of new DNA markers, in particular 141 bp fragment of cauliflower mosaic virus (CaMV) 35S promoter, 224 bp fragment of Agrobacterium tumefaciens nopaline synthase (NOS) terminator, 256 bp fragment of 5-enolppyruvylshikimate-phosphate synthase (epsps) gene and 258 bp fragment of Cry1Ab delta-endotoxin (cry1Ab) gene for GMO screening. The certified reference materials containing Roundup Ready soybean (RRS) and maize MON 810 were applied for the development and optimization of uniplex and multiplex PCR systems. Evaluation of amplification products by agarose gel electrophoresis using negative and positive controls confirmed high specificity and sensitivity at 0.1% GMO for both RRS and MON 810. The fourplex PCR was developed and optimized that allows simultaneous detection of three common transgenic elements, such as: CaMV 35S promoter, NOS terminator, epsps gene together with soybean-specific lectin gene. The triplex PCR developed enables simultaneous identification of transgenic elements, such as: 35S promoter and cry1Ab gene together with maize zein gene. The analysis of different processed foods demonstrated that multiplex PCR methods developed in this study are useful for accurate and fast screening of GM food products.